Perancangan Corporate Identity melalui Media Komunikasi Visual pada Distributor Sumber Jaya Toys Store - Meta Saharani; Adam Wahida; Margana (Lembaga Penelitian Pengembangan dan Pengabdian Kepada Masyarakat STMIK Asia Malang, 2025)
Sumber Group has a special brand for its toy business sector, namely Sumber Jaya Toys Store and Sumber Mas Accessories to shelter its fashion accessories. Each of its business sectors has a different logo identity. The existence of two brand logos other than the company's main logo makes it difficult for some target markets to differentiate the two business sectors they are in. The design of this corporate identity is carried out to further strengthen the image of Sumber Jaya Toys Store as a brand that distributes local and imported toys. This research uses Research and Development (R&D) research methods that refer to the research stage by Sugiono, including potential and problem analysis, data collection, product design, design validation, design revision, limited-scale trials and wide-scale trials. The results of this development research are corporate identity products with a fun and playful company minimalist design style in the form of business cards, company calendars, brochures, id cards, member cards, uniforms, and content for Instagram social media.